Codon optimized influenza H1 HA sequence but not CTLA-4 targeting of HA antigen to enhance the efficacy of DNA vaccines in an animal model - Dito Anurogo; Chia-Yuan Chen; Chu-Chi Lin; Jeanne Adiwinata Pawitan; Daniel W. Qiu; J. Timothy Qiu (Journal of Immunotoxicology)
Infections caused by the influenza virus lead to both epidemic and pandemic outbreaks in humans and animals. Owing to their rapid production, safety, and stability, DNA vaccines represent a promising avenue for eliciting immunity and thwarting viral infections. While DNA vaccines have demonstrated substantial efficacy in murine models, their effectiveness in larger animals remains subdued. This limitation may be addressed by augmenting the immunogenicity of DNA-based vaccines. In the investigation here, protein expression was enhanced via codon optimization and then mouse cytotoxic T-lymphocyte antigen 4 (CTLA-4) was harnessed as a modulatory adjunct to bind directly to antigen-presenting cells. Further, the study evaluated the immunogenicity of two variants of the hemagglutinin (HA) antigen, i.e. the full-length and the C-terminal deletion versions. The study findings revealed that the codon-optimized HA gene (pcHA) led to increased protein synthesis, as evidenced by elevated mRNA levels. Codon optimization also significantly bolstered both cellular and humoral immune responses. In cytokine assays, all plasmid constructs, particularly pCTLA4-cHA, induced robust interferon (IFN)-γ production, while interleukin (IL)-4 levels remained uniformly non-significant. Mice immunized with pcHA displayed an augmented presence of IFNγ+ T-cells, underscoring the enhanced potency of the codon-optimized HA vaccine. Contrarily, CTLA-4-fused DNA vaccines did not significantly amplify the immune response.